Desain dan Analisis Elemen Hingga Model Prosthetic Ankle-Foot - Zakki Fuadi Emzain; Utsman Syah Amrullah; AM Mufarrih (P3M Politeknik Negeri Cilacap, 2020)
Foot prosthetics is one of the needs of the disabled feet as a tool for activities. The ankle prosthetic model is proposed as an alternative prosthetic model that is affordable to people with disabilities. The model is designed and analyzed to be able to withstand the average weight of a human being in the heel strike, midstance, and toe-off position and has a safe safety factor value. The research method used is the model design and model analysis consisting of preprocessing, solution, and post-processing. The analysis results showed that the greatest deformation occurred in the toe-off position of 1.52 mm when given a load of 500 N and 0.036 mm when given a moment of 5000 Nmm. The greatest strain energy was located in the forefoot area at a toe-off position of 0.6 mJ. Maximum stress also occurred at the toe-off position of 5.71 MPa. With a safety factor of 4.7, this model is categorized as safe because the stress that occurs is still below the yield strength limit of the ABS material.